The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.5902/1980509833367
|View full text |Cite
|
Sign up to set email alerts
|

TÉCNICAS DE ANÁLISE DE IMAGEM PARA CARACTERIZAÇÃO DA QUALIDADE DE SEMENTES DE PARICARANA (<i>Bowdichia virgilioides </i>Kunth)

Abstract: A Bowdichia virgilioides Kunth., conhecida popularmente como paricarana, é uma espécie com potencial econômico paisagístico, madeireiro e para a recuperação de áreas degradadas. Objetivou-se com este trabalho a caracterização física de sementes de paricarana com diferentes cores do tegumento provenientes de 12 matrizes, utilizando técnicas de análise de imagem, além de verificar a eficiência do tratamento de superação de dormência aplicado às sementes para determinar a qualidade fisiológica. As sementes de 12 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 11 publications
(12 reference statements)
1
11
0
1
Order By: Relevance
“…Variables based on pixel intensity, such as relative density, integrated density, and median gray, have been used to classify seeds within physical quality levels (Abud et al, 2018;Arkhipov et al, 2020;Medeiros et al, 2018). These variables are calculated using the gray values of each pixel in the image and have a direct relationship to the resistance that the internal tissues of the seed present to the X-ray passage (Kotwaliwale et al, 2014). Thus, higher intensities of gray indicate denser tissues, i.e., there is a higher impediment to the X-ray passage, which confer a higher level of radiopacity in the seed radiography.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Variables based on pixel intensity, such as relative density, integrated density, and median gray, have been used to classify seeds within physical quality levels (Abud et al, 2018;Arkhipov et al, 2020;Medeiros et al, 2018). These variables are calculated using the gray values of each pixel in the image and have a direct relationship to the resistance that the internal tissues of the seed present to the X-ray passage (Kotwaliwale et al, 2014). Thus, higher intensities of gray indicate denser tissues, i.e., there is a higher impediment to the X-ray passage, which confer a higher level of radiopacity in the seed radiography.…”
Section: Resultsmentioning
confidence: 99%
“…Bars represent the standard deviation. The level of X-ray absorption by seeds is mainly determined by the factors composition, thickness, and density of seed tissues and the wavelength of ionizing radiation (Kotwaliwale et al, 2014). Some studies have mentioned that the contrast used by the equipment in the image calibration must be standardized for a precise comparison between variables related to pixel intensity .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This occurs because these seeds have some wraps, among them, waxy cuticle, suberin, palisade tissue and the macrosclereid layers (Cardoso, 2004). Lima et al (2018), performing image analysis technique in Bowdichia virgilioides Kunth, observed that this species may show different seed coat thicknesses.…”
Section: Methodsmentioning
confidence: 99%
“…Some software has been developed to assist in computerized analysis of seedlings and allow inferences to be made regarding seed vigor. Prominent among them are the Seed Vigor Imaging System (SVIS®) (Sako, McDonald, Fujimura, Evans, & Bennett, 2001;Trujillo, Gomes-Junior & Cicero, 2019), the automated seed vigor system (Sistema automatizado do vigor de sementes -Vigor-S®) (Castan et al, 2018;Medeiros, Silva, Capobiango, Fialho & Dias, 2019b), GroundEye® (Lima, Smiderle, Oliveira & Carvalho, 2018), and the seedling analysis system (Sistema de análise de plântulas -SAPL®) . However, this last system mentioned was designed to use a more accessible image acquisition system, based on digital images obtained by digital cameras or even smartphones, and its software is free for processing seedling images.…”
Section: Introductionmentioning
confidence: 99%